Engaging Students in Large Health Classes with Active Learning Strategies. Issue 6 (24th July 2017) - Elliott, Steven; Combs, Sue; Huelskamp, Amelia; Hritz, Nancy
Abstract : Creative K-12 health teachers can engage students in large classes by utilizing active learning strategies. Active learning involves engaging students in higher-order tasks, such as analysis and synthesis, which is a crucial element of the movement toward what is commonly called "learner-centered" teaching. Health education teachers who develop student learning outcomes based on higher-order objectives on Bloom's taxonomy often construct more engaging, learner-centered activities to facilitate achievement of those outcomes. Relatedly, current best practices in health education emphasize the use of strategies designed to personalize and engage students in developing the essential health skills necessary to adopt, practice and maintain health-enhancing behaviors. There are multiple teaching strategies that can be employed in large classes to preserve an active learning environment that fosters student engagement. The purpose of this article is to describe some of the strategies that would be most applicable to a health class to help students meet state standards and the National Health Education Standards.